Death, desire and loss in western culture - Dollimore, Jonathan (New York : Routledge, 2001)
Death, Desire and Loss in Western Culture is a rich testament to our ubiquitous preoccupation with the tangled web of death and desire. In these pages we find nuanced analysis that blends Plato with Shelley, Hölderlin with Foucault. Dollimore, a gifted thinker, is not content to summarize these texts from afar; instead, he weaves a thread through each to tell the magnificent story of the making of the modern individual.
I. The Ancient World. 1. Eros and Thanatos, Change and Loss in the Ancient World. 2. 'All Words Fail through Weariness': Ecclesiastes. 3. Escaping Desire: Christianity, Gnosticism and Buddhism
II. Mutability, Melancholy and Quest: The Renaissance. 4. Fatal Confusions: Sex and Death in Early Modern Culture. 5. 'Death's Incessant Motion'. 6. Death and Identity. 7. 'Desire is Death': Shakespeare
III. Social Death. 8. The Denial of Death? 9. Degeneration and Dissidence. 10. Between Degeneration and the Death Drive: Joseph Conrad's Heart of Darkness
IV. Modernity and Philosophy: The Authenticity of Nothingness. 11. The Philosophical Embrace of Death: Hegel. 12. Heidegger, Kojeve and Sartre
V. The Desire not to be: Late Metaphysics and Psychoanalysis. 13. Dying as the Real Aim of Life: Schopenhauer. 14. Freud: Life as a Detour to Death
VI. Renouncing Death. 15. The Philosophy of Praxis and Emancipation: Feuerbach, Marx, Marcuse
VII. The Aesthetics of Energy.
16. Fighting Decadence: Nietzsche against Schopenhauer and Wagner. 17. Ecstasy and Annihilation: Georges Bataille. 18. In Search of Potency: D. H. Lawrence
VIII. Death and the Homoerotic. 19. Wrecked by Desire: Thomas Mann. 20. Promiscuity and Death. 21. The Wonder of the Pleasure.
Str. 356-374: Bibliografija
Kazalo
Keywords: eros; thanatos; kultura; kultura zapada; filozofija; psihologija; smrt